Electronic Bottleneck Suppression in Next‐Generation Networks with Integrated Photonic Digital‐to‐Analog Converters. Issue 2 (23rd November 2020) - Meng, Jiawei; Miscuglio, Mario; George, Jonathan K.; Babakhani, Aydin; Sorger, Volker J.
Abstract : Digital‐to‐analog converters (DAC) are indispensable functional units in signal processing instrumentation and wide‐band telecommunication links for both civil and military applications. As photonic systems are capable of high data throughput and low latency, an increasingly found system limitation stems from the required domain crossing such as digital to analog and electronic to optical. A photonic DAC implementation, in contrast, enables a seamless signal conversion with respect to both energy efficiency and short signal delay, often requiring bulky discrete optical components and electric–optic transformation, hence introducing inefficiencies. Herein, a novel coherent parallel photonic DAC concept along with a 4‐bit experimental prototype capable of performing this DAC without optic–electric–optic domain crossing is introduced. This new paradigm guarantees a linear intensity weighting among bits when operating at high sampling rates (50 GHz), featuring an exceptional sampling efficiency (> 100 GS J − 1 ) and small footprint (≈1 mm 2 ) in an 8‐bit implementation. Importantly, this photonic DAC enables seamless interfaces of next‐generation data processing hardware with high relevance in data centers, task‐specific compute accelerators such as neuromorphic engines, and network edge processing applications. Abstract : Herein, domain crossings from digital‐to‐analog signals and from electronics to optics by introducing a photonic parallel binary‐weighting digital–analog converter (DAC) in silicon photonics technology are introduced. Results show a higher sampling efficiency and smaller chip footprint when compared to electronic DACs. This is potentially revolutionary as it enables the seamless interfaces of next‐generation data processing hardware.